Regular exercise alleviates renovascular hypertension-induced cardiac/endothelial dysfunction and oxidative injury in rats - (:unkn) unknown (My University, 2016)
The importance of physical activity in the management of renovascular diseases is well-known, but lacks evidence of underlying mechanisms. The purpose of the study was to elucidate the protective/therapeutic effects of regular exercise on experimental renovascular hypertension (RVH)-induced oxidative stress and cardiac dysfunction. Wistar albino rats underwent a RVH surgery (2K1C, Goldblatt). Three weeks later half of the rats started swimming exercise for 9 weeks (n = 15), while the sedentary RVH group (n = 15) had no exercise during that period. Sham-operated control rats (n = 10), had the similar surgical procedures but the left renal artery was left unclipped. Body weights were monitored, and blood pressures were measured weekly using tail-cuff. Echocardiographic evaluation was performed on the 3(rd) week and on the 12(th) week of the experiment before the rats were decapitated. Heart and thoracic aorta were removed and serum was collected, while aortic samples were put in a 10% formaldehyde solution for immunochemistry. Cardiac tissue samples obtained from each animal were used for the determination of tissue myeloperoxidase (MPO) and catalase (CAT) activities, malondialdehyde (MDA), and glutathione (GSH) levels. In the sedentary RVH group, aortic contractile response (contraction/relaxation in isolated organ bath), left ventricular diastolic and systolic dimensions, and immunohistochemical staining of aortic inducible nitric oxide synthase (iNOS) were increased, while ejection fraction and aortic endothelial nitric oxide synthase (eNOS) staining were decreased. RVH in the sedentary rats resulted in increased pro-inflammatory cytokines (TNF-α, IL-2, IL-6), lipid peroxidation (malondialdehyde) and neutrophil infiltration (myeloperoxidase activity) along with reductions in antioxidant glutathione and catalase levels in the cardiac tissue. Exercise after RVH increased the immunohistochemical staining of aortic eNOS, decreased iNOS staining and reversed the alterations in echocardiographic and oxidative parameters. Regular exercise commenced after RVH surgery alleviated renovascular hypertension-induced oxidative injury, by modulating oxidant-antioxidant balance via the involvement of the endothelial NO system.
Keywords: Tumor Necrosis Factor-alpha; Animals; Male; Rats; Blood Pressure; Antioxidants; Heart; Rats, Wistar; Glutathione; Lipid Peroxidation; Malondialdehyde; Oxidative Stress; Nitric Oxide Synthase Type III; Catalase; Interleukin-6; Nitric Oxide; Nitric Oxide Synthase Type II; Neutrophils; Oxidation-Reduction; Physical Conditioning, Animal; Hypertension, Renovascular; Interleukin-2; Endothelium